(untitled) (Journal of Bio-Science, 2018)
Biodiesel is a non-toxic and very low sulfur containing, renewable and biodegradable diesel fuel substitute with low volatility and high cetane number. It is derived from fresh or waste vegetable oils and animal fats transesterified with short chain alcohol such as ethanol or methanol in the presence of a catalyst. Several new types of carriers and technologies have been adopted in the recent past to improve the ability of a catalyst in transesterification. One of the new trends is nanoparticles-based immobilization of enzyme as a catalyst. The combination of the precise physical, chemical, optical and electrical properties of nanoparticles with the specific recognition site or catalytic properties has led them to appear in a myriad of novel nanomaterial application. Enzyme immobilized on nanoparticles showed a broader working temperature and pH range and thermal stability than the native enzyme. Enhancement in the reactivity of nanocatalysts is associated with their increased surface area, greater concentrations of highly reactive edge, unusual and stabilized lattice planes. The greater activity of nanomaterial immobilized biocatalyst affords operational simplicity, low energy consumption, and greater safety, in the process of transesterification. This review article highlights the issues including the exploration of the ability of nanomaterial to immobilize biocatalyst and factors that influence the activity of biocatalysts upon immobilization. J. bio-sci. 23: 01-17, 2015